PERANCANGAN NOVEL GRAFIS MENGENAI KEPRIBADIAN LANSIA UNTUK MENINGKATKAN INTERAKSI SERTA DUKUNGAN SOSIAL ANTARA REMAJA DENGAN LANSIA - Arum Nastiti Karnain (Jurnal Nawala Visual, 2022)
Social support is a need of the eldery, such as emotioinal support where the eldery will have safe feeling, comfortable, valued, and needed. But without interaction, this feeling will not grow. At the age of adolescene, teenagers are the most possible group that have time to interact with the eldery, first they will face their grandparents, and when they grow up, they will face their parents whos geting older. Unfortunately, the teenagers has lack of understanding about the personality of the eldery, this affects how teenagers response to the behavior of the eldery, so more less interaction they made. This graphic novel about the personality of the eldery is desinged to increase awarness of teenagers about the eldery, to improve the welfare of the eldery and preparing teenagers entering the old age in the future. The reserach methode is using qualitative, data collected by observation, interviews, and survey. Then with the presence of a graphic novel of personalities of the eldery will increase awareness and interaction between teenagers and the eldery.